Smoking and environmental characteristics of smokers with a mental illness, and associations with quitting behaviour and motivation; a cross sectional study. (December 2016) - Metse, Alexandra; Wiggers, John; Wye, Paula; Moore, Lyndell; Clancy, Richard; Wolfenden, Luke; Freund, Megan; Van Zeist, Tara; Stockings, Emily; Bowman, Jenny
Abstract Background Persons with a mental illness are less likely to be successful in attempts to quit smoking. A number of smoking and environmental characteristics have been shown to be related to quitting behaviour and motivation of smokers generally, however have been less studied among smokers with a mental illness. This study aimed to report the prevalence of smoking characteristics and a variety of physical and social environmental characteristics of smokers with a mental illness, and explore their association with quitting behaviour and motivation. Methods A cross-sectional descriptive study was undertaken of 754 smokers admitted to four psychiatric inpatient facilities in Australia. Multivariable logistic regression analyses were undertaken to explore the association between smoking and environmental characteristics and recent quitting behaviour and motivation. Results Participants were primarily daily smokers (93 %), consumed >10 cigarettes per day (74 %), and highly nicotine dependent (51 %). A third (32 %) lived in a house in which smoking was permitted, and 44 % lived with other smokers. The majority of participants believed that significant others (68–82 %) and health care providers (80–91 %) would be supportive of their quitting smoking. Reflecting previous research, the smoking characteristics examined were variously associated with quitting behaviour and motivation. Additionally, participants not living with other smokers were more likely to have quit for a longer duration (OR 2.02), and those perceiving their psychiatrist to be supportive of a quit attempt were more likely to have had more quit attempts in the past six months (OR 2.83). Conclusions Modifiable characteristics of the physical and social environment, and of smoking, should be considered in smoking cessation interventions for persons with a mental illness.